The use of Ellis pins (negative profile tip-threaded pins) in external skeletal fixation in dogs and cats - Beck, A. L.; Pead, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The Ellis pin is commonly used in external skeletal fixators (ESFs) but some authors suggest that this pin suffers from a high rate of failure. The purpose of this study was to look for complications associated with four different pin types, in particular pin breakage, as well as pin loosening, radiolucency around pins and pin tract discharge. Fifty consecutive cases which had an ESF applied using Ellis pins were identified. Radiographs and case records were used to record case details, ESF design, duration of fixation, pin types used, and complications. Records from 31 dogs and 17 cats were examined (2 animals were removed from the study because of incomplete follow-up). There were 21 Type I, 7 Type I with a tied-in IM pin, 2 modified Type I, 2 modified Type I with a tied-in IM pin and 16 modified Type II ESFs. 160 Ellis pins, 30 centrally threaded positive profile pins, 4 end threaded positive profile pins and 46 smooth pins were used. Complications relating to one or more of the pins were seen in 65% of the fixators. None of the pins broke. There was a significant association between individual pin type and the number of pins showing loosening (p = 0.002) or radiolucency (p = 0.006), but not a significance in the association between pin type and discharge (Chi-Square test). When each pin was compared against each other pin, smooth pins were significantly more likely to be loose than Ellis pins (p <0.001), and centrally threaded positive profile pins were significantly more likely to result in radiolucency than Ellis pins (p = 0.01), using a Chi-square test. There was not any significant association between any other pin types for any complication using a Fisher’s Exact test. The study demonstrates that Ellis pins, when inserted correctly, are not at any greater risk of failure than other pin types, and that fewer complications may be associated with them than other pin designs.
Keywords: External skeletal fixation; Ellis pin; radiolucency; pin loosening